Hepatitis C seropositivity in lichen planus: a case control study in a tertiary care hospital - Narendra, Gangaiah; Ahmed, Mowazaffin; Amruthavalli, Potlapati; Shivanna, Raghunatha (International Journal of Research in Dermatology, 2020)
Background: Lichen planus (LP), an immune-mediated disorder, has been reported as an extra-hepatic manifestation of Hepatitis C virus (HCV) infection, especially in HCV hyper endemic areas such as southern Europe and Japan. In India, the association between LP and HCV is documented in many studies. The aim of this study was to investigate hepatitis C virus infection in patients with lichen planus from an epidemiological standpoint and determine the sero-positivity of hepatitis C virus in patients with lichen planus and also to describe clinical profile of lichen planus in patients with hepatitis C virus infection. Methods: This hospital-based case control study was conducted over 167 patients and 167 controls, evaluation included detailed history, cutaneous examination, routine blood tests and ELISA test for seropositivity. Results: In this case control study 5.4% of the total study population presented with hepatitis c infection. Hepatitis C infection was more common in oral LP out of all the HCV positivity obtained in LP patients. Male to female ratio was 1:2.2. Prevalence of HCV infection was found to be slightly more in cases (6.6%) than controls (4.2%) but there is no statistically significant difference in the prevalence of HCV infection among cases and controls. Conclusions: In conclusion, from the evaluation of our epidemiological data, any etiological link between LP and HCV could not be found in our population and an etiological link between LP and HCV cannot be inferred solely by epidemiological data.